2019
DOI: 10.1002/adhm.201900965
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Porous Microspheres Dry Powders for Codelivery of Afatinib‐Loaded Solid Lipid Nanoparticles and Paclitaxel: Novel Therapy for EGFR Tyrosine Kinase Inhibitors Resistant Nonsmall Cell Lung Cancer

Abstract: Combination therapy of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR TKIs) with other chemotherapeutic agents is a feasible strategy to overcome resistance that often occurs after 9–13 months of EGFR TKIs administration in nonsmall cell lung cancer (NSCLC). In this study, a pulmonary microspheres system that codelivers afatinib and paclitaxel (PTX) is developed for treatment of EGFR TKIs resistant NSCLC. In this system, afatinib is loaded in stearic acid‐based solid lipid nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…The results of the study showed that AFT and PTX have a synergistic effect and show excellent therapeutic effects in drug-resistant NSCLC cells. In vivo experiments have shown that PTX and AFT can maintain high concentrations in the lungs for 96 h. This drug delivery strategy provides research directions for EGFR TKI-resistant lung cancer [81].…”
Section: Nanomedicine and Anticancer Drugsmentioning
confidence: 92%
“…The results of the study showed that AFT and PTX have a synergistic effect and show excellent therapeutic effects in drug-resistant NSCLC cells. In vivo experiments have shown that PTX and AFT can maintain high concentrations in the lungs for 96 h. This drug delivery strategy provides research directions for EGFR TKI-resistant lung cancer [81].…”
Section: Nanomedicine and Anticancer Drugsmentioning
confidence: 92%
“…These inhaled microspheres systems are characterized with D ae , FPF, fine particle dose (FPD), and GSD of 3.26 and 3.25 µm, 23.04 and 24.07%, 41.01 and 59.66 µg, 2.26 and 2.32, as well as EE% 53–70.85% of afatinib and paclitaxel, respectively. These final formulations showed an initial in vitro drug release for paclitaxel (20%) and afatinib (30%), with extremely high retention (more than 65%) in the induction port (17.21 ± 0.22% for afatinib and 16.00 ± 1.52% for paclitaxel), and no interaction between drugs and carriers when characterized by FTIR and NMR spectroscopy [ 126 ]. On the cellular level, there was a significant synergistic effect between afatinib and paclitaxel and superior treatment capability of the final loaded microspheres for drug-resistant NSCLC on H1975 and PC9/G cells.…”
Section: Inhalable Anticancer Drug-loaded Lipid-based Nanocarriersmentioning
confidence: 99%
“…Large porous particles (LPPs), by virtue of their porosity, exhibit an aerodynamic diameter much smaller than their geometric size, facilitating excellent flowability and improved dispersion ( Edwards et al, 1997 ). For example, the emulsion evaporation method enables the production of light porous particles that display an improved flowability and deep lung deposition ( Yang et al, 2019 ). Therefore, LPPs are highly efficient in the delivery of inhaled therapeutics into the systemic circulation ( Zhang et al, 2018 ).…”
Section: Advancements On Dpi Formulationsmentioning
confidence: 99%